Perbandingan Algoritma Reduksi Tipe pada Fuzzy Tipe-2 - Humaira, Mira (Department of Informatics Engineering, 2014)
Type-2 Fuzzy became populer because itâ€™s capability handles uncertainty more better. It effects computational cost. This research insurance that there is algorithm having good performance ie. EIASC. It has short time if count of N is small. Â Index Termsâ€”EIASC Algorithm, Type-2 Fuzzy